Factor in quadratic form.

## How do you factor x^2(x+2)-(x+2) ?

Tutors, please sign in to answer this question.

# 2 Answers

x^{2}(x + 2) - (x + 2)

Notice that there is a greatest common factor (gcf) that you can factor out of the entire equation, that being: x + 2

x^{2}(x + 2) - 1(x + 2) ==> (x + 2) ( x^{2}(1) - 1(1) ) ==> (x + 2)(x^{2} - 1)

Thus, x^{2}(x + 2) - (x + 2) = (x^{2} - 1)(x + 2)

x^{2}(x+2)-(x+2)

= (x+2)(x^{2}-1), factor out x+2 first

= (x+2)(x+1)(x-1), since x^{2}-1 = (x+1)(x-1)